Wortbildung und Kategorisierung am Beispiel der desubstantivischen Wortbildung des Russischen - Kakridis, Yannis (Slavistische Beitraege, 1999)
This study is dedicated to the analysis and categorization of derived words of Russian; Their concern can be summarized in two questions: a) what part does the word formation meaning have in the lexical meaning of the derived word? b) What are the semantic building blocks of the word formation system of a language (its word formation categories)?